Dr M meets Anwar in closed-door meeting - News Straits, Times (New Strait Times, 2017)
KUALA LUMPUR: Tun Dr Mahathir Mohamad yesterday met former archnemesis Datuk Seri Anwar Ibrahim to propose the possibility of jointly leading the opposition in the next general election,amid accusations lobbed at the former prime minister over a series of about turns.